Human Placenta-Derived Mesenchymal Stem Cells Reduce Mortality and Hematoma Size in a Rat Intracerebral Hemorrhage Model in an Acute Phase - Bo Young Choi; Ok Joon Kim; Sae-Hong Min; Jeong Hyun Jeong; Sang Won Suh; Tae Nyoung Chung (Stem Cells International)
Intracerebral hemorrhage (ICH) is a critical disease, highly associated with mortality and morbidity. Several studies have demonstrated the beneficial effect of mesenchymal stem cells (MSCs) on ICH, mostly focused on their mid-to-long-term effect. Acute hematoma expansion is one of the most important prognostic factors of ICH. We hypothesized that MSCs would decrease mortality and hematoma size in acute ICH, based on the findings of a few recent researches reporting their effect on blood-brain barrier and endothelial integrity. Rat ICH models were made using bacterial collagenase. One hour after ICH induction, the rats were randomly divided into MSC-treated and control groups. Mortality, hematoma volume, ventricular enlargement, brain edema, and degenerating neuron count were compared at 24 hours after ICH induction. Expression of tight junction proteins (ZO-1, occludin) and coagulation factor VII mRNA was also compared. Mortality rate (50% versus 8.3%), hematoma size, ventricular size, hemispheric enlargement, and degenerating neuron count were significantly lower in the MSC-treated group (p=0.034, 0.038, 0.001, 0.022, and <0.001, resp.), while the expression of ZO-1 and occludin was higher (p=0.007 and 0.012). Administration of MSCs may prevent hematoma expansion in the hyperacute stage of ICH and decrease acute mortality by enhancing the endothelial integrity of cerebral vasculature.